Analysis of Development and Implementation of Web-Based ERP at DTC Company - Sinulingga, Timothy Oktavianus; Setiawan, Ari (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This research explores the development and implementation of a web-based ERP system at PT Datacomm, in response to the needs of digital transformation in the modern business world. The purpose of this research is to understand how ERP systems can integrate business processes and improve organizational performance. The method used is a qualitative case study, with data collection through in-depth interviews, participatory observation, and document analysis from 15 respondents, including project team members and senior management. The results showed that ERPNext significantly improved operational efficiency by reducing manual tasks and improving reporting accuracy. The system is also flexible to adapt to workflows and has an intuitive interface that increases user satisfaction. However, there were some challenges in integrating ERPNext with legacy systems as well as the need for ongoing training for users. In conclusion, ERPNext is an appropriate solution to improve operational performance, although continuous improvement in terms of integration and training is required to maximize the system's potential. This research provides practical insights for ERP implementation strategies as well as recommendations for organizations looking to adopt similar initiatives.